Comparison between Two Local Thermal Non Equilibrium Criteria in Forced Convection through a Porous Channel - azzedine ABDEDOU; Khedidja Bouhadef (Journal of Applied Fluid Mechanics, 2015)
Two criteria are used and compared to investigate the local thermal equilibrium assumption in a forced convection through a porous channel. The first criterion is based on the maximum local temperature difference between the solid and fluid phases, while the second is based on the average of the local differences between the temperature of the solid phase and the fluid phase. For this purpose, the momentum and energy equations based on the Darcy-Brinkman-Forchheimer and the local thermal non equilibrium models are solved numerically using the finite volume method. The analysis focused on searching thermophysical parameters ranges which validate local thermal equilibrium hypothesis. Thus, by using the two criteria, the obtained results mainly revealed that this local thermal equilibrium assumption is verified for low thermal conductivity ratio and Reynolds number values and for high interstitial Biot number and porosity, while it is unfavorably affected by the high values of Prandtl number. However, it is also found that the parameters ranges corresponding to the local equilibrium validity depends on the selected local thermal non equilibrium criterion.